Determinants of future earnings: UK publicly listed companies - ZHU, Jinxin (2016)
This paper tried to use cross-sectional models based on model developed by Hou, van Dijk and Zhang (2012) to forecast earnings of listed companies in the UK market. This paper has eight sections. The introduction mainly introduced the meaning of forecasting and methods to forecast. The literature review section introduced the research achievements and contributions made by researchers in forecasting area and how each forecasting methods used by scholars. In the research question and development of hypotheses section, I illustrated every hypotheses and how to test these hypotheses. The next section is data and empirical methodology, I explained how to choose and get data and how to select holdout sample and test sample. Besides, I introduced how to test and solve heteroscedasticity and how to test performs of model. The next section is analysis part. In this part I explained details of the summary of data (samples) and regression results firstly. Then I introduced test and solution about heteroscedasticity comprehensive, including White test and FGLS (Feasible Generalised Least Squares). Thirdly, I interpreted how to use several indictors to conduct errors analysis. After the errors analysis, I tried to use a new cross-sectional model to fit UK market better. The third last part is supplementary test. I used a deflated model to test if this model is better than the previous models. In the conclusion, I summarized this paper and introduced the limitation and directions for further researches. The last section is references.